Penerapan model PBL materi aplikasi gelombang elektromagnetik hasil analisis kontaminan daging menggunakan metode spektroskopi - Ria Aprilia; Nirwana Nirwana; M. Lutfi Firdaus (PendIPA Journal of Science Education, 2019)
ABSTRACT[Implementation PBL model in electromagnetic wave material from analysis result of meat contaminant with spectroscopy method]. The aims at this study was to explain differences in learning outcomes between students who study with Problem Based Learning Learning Model (PBL) with students who study conventionally on Electromagnetic Waves material. This method of educational research used quasi experimental research methods. The design of this research is pretest-posttest control group design. Population in this research is all class X SMA Negeri 9 Lubuklinggau, which consists of 4 classes and selected as sample is class X.1 as experiment class and X.2 as control class. Technique of collecting data used is test. The hypothesis of this study is that there are differences in learning outcomes between students learning to use Problem Based Learning (PBL) learning model with students who study conventionally in Physics learning at SMA Negeri 9 Lubuklinggau. Differences can be seen from the results of the mean values of the control and experimental classes, the control class has an average grade value of 80.09 and the experimental class has an average value of 87.25. Based on result of analysis obtained from t test, that is tcount bigger than ttable with value 4,64 > 1,68 then H0 refused and Ha accepted. Thus the hypothesis proposed in this study accepted the truth. Keywords: Learning Outcomes; Problem Based Learning (PBL); Electromagnetic Waves; Spectroscopy. (Received February 20, 2018; Accepted July 15, 2019; Published October 8, 2019) AbstrakPenelitian ini bertujuan untuk menjelaskan perbedaan hasil belajar antara siswa yang belajar dengan Model Pembelajaran Problem Based Learning (PBL) dengan siswa yang belajar secara konvensional pada materi Gelombang Elektromagnetik. Metode penelitian pendidikan ini menggunakan metode penelitian eksperimen semu. Desain penelitian ini adalah pretest-posttest control group design. Populasi dalam penelitian ini adalah seluruh kelas X SMA Negeri 9 Lubuklinggau, yang terdiri dari 4 kelas dan yang terpilih sebagai sampel adalah kelas X.1 sebagai kelas eksperimen dan X.2 sebagai kelas kontrol. Teknik pengumpulan data yang digunakan adalah tes. Hipotesis penelitian ini adalah ada perbedaan hasil belajar antara siswa yang belajar menggunakan model pembelajaran Problem Based Learning (PBL) dengan siswa yang belajar secara konvensional pada pembelajaran Fisika di SMA Negeri 9 Lubuklinggau. Perbedaan dapat dilihat dari hasil nilai rata-rata kelas kontrol dan eksperiman, kelas kontrol memiliki nilai rata-rata kelas 80,09 dan kelas eksperimen memiliki nilai rata-rata 87,25. Berdasarkan hasil analisis yang diperoleh dari uji t, yaitu thitung  lebih besar daripada ttabel dengan nilai 4,64 > 1,68 maka H0 ditolak dan Ha diterima. Dengan demikian hipotesis yang diajukan dalam penelitian ini diterima kebenarannya.Kata kunci: Hasil Belajar; Problem Based Learning (PBL); Gelombang Elektromagnetik; Spektroskopi.